PERBANDINGAN METODE REMEDIASI UNTUK MENGATASI LIMBAH LOGAM BERAT - Octavia, Mutia Nurul (rc-institut, 2019)
This study aims to determine the various types of remediation techniques, to determine the dangers of heavy metals to the environment and to determine the weaknesses and strengths of each method. This paper will discuss three methods of chemical soil remediation which include soil flushing, soil washing and solidification/ stabilization techniques. From the three techniques discussed, it is known that solidification / stabilization techniques are suitable techniques for effectively reducing heavy metal waste.